2017
DOI: 10.1186/s12983-017-0248-3
|View full text |Cite
|
Sign up to set email alerts
|

Different feeding strategies in Antarctic scavenging amphipods and their implications for colonisation success in times of retreating glaciers

Abstract: BackgroundScavenger guilds are composed of a variety of species, co-existing in the same habitat and sharing the same niche in the food web. Niche partitioning among them can manifest in different feeding strategies, e.g. during carcass feeding. In the bentho-pelagic realm of the Southern Ocean, scavenging amphipods (Lysianassoidea) are ubiquitous and occupy a central role in decomposition processes. Here we address the question whether scavenging lysianassoid amphipods employ different feeding strategies duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 66 publications
0
17
0
1
Order By: Relevance
“…Such species' molars therefore do not have a grinding function, but can serve to push pieces of food into the stomodeum when the mandible is adducted (Steele & Steele 1993). Members of the second functional group have a continuous and less rapid feeding behaviour and probably do not survive long starvation periods (Seefeldt et al 2017). The mandibles of these usually smaller species bear a slender incisor process and a triturative molar (Sainte-Marie 1984, Momo et al 1998, Arndt et al 2005, Seefeldt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such species' molars therefore do not have a grinding function, but can serve to push pieces of food into the stomodeum when the mandible is adducted (Steele & Steele 1993). Members of the second functional group have a continuous and less rapid feeding behaviour and probably do not survive long starvation periods (Seefeldt et al 2017). The mandibles of these usually smaller species bear a slender incisor process and a triturative molar (Sainte-Marie 1984, Momo et al 1998, Arndt et al 2005, Seefeldt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the molar suggests that these animals rely on a broader dietary regime (Sainte-Marie 1984). This group would therefore be composed of more facultative scavengers that could also act as predators and/or deposit feeders (Seefeldt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on subterranean amphipods has shown that morphologically cryptic species in fact occupied very distinct feeding niches ranging from predation to filter-feeding (Fišer et al 2015). Furthermore, also within the scavenging guild, distinct succession patterns linked to feeding strategies (carcass "openers" vs. "squeezers") and morphological adaptations to opportunistic or obligate carrion-feeding, may allow niche partitioning amongst closely related lysianassoids (Seefeldt et al 2017b). In this context, in-depth morphological investigations based on scanning electron microscopy of the feeding apparatus (e.g., a mouthpart-atlas, Arndt et al 2005), as well as feeding experiments characterizing feeding rates and preferences (Seefeldt et al 2017b), can elucidate subtly different feeding methods within the scavenging guild.…”
Section: Taxonomic Problems and Cryptic Species As An Impediment For mentioning
confidence: 99%
“…They dwell in sheltered sites, almost exclusively under flat, loose stones, making specimens readily available to volunteers at low tide. Scientists had previously conducted research demonstrating that the two species compete for space (Weslawski, 1990). However, in that study only a single fjord was investigated.…”
Section: Project Introductionmentioning
confidence: 99%